AIN NI AIN: Kajian Sosio-Kultural Masyarakat Kei Tentang Konsep Hidup Bersama Dalam Perbedaan - Elly Esra Kudubun (Cakrawala Jurnal Penelitian Sosial, 2016)
Ain Ni Ain philosophy that symbolized as "fish" and " Bird" means eventhough the peopleof Kei have classified into various groups, the classification according by the powerinterest and regional, as well as the interests of level, and religion, but they are one in apower- kinship.Even fish comes from a small community though, it still able to adapt to the other fisharound. It's a sign that, Kei people is easy to unite and to mingle with others in selfconfidence. Also the egg-laying birds as a symbol of unextinction people in Kei Islandswho will always have their descendant to inherit all the ancestral deal about Ain ni Aincontained in Customary Law Larvul Ngabal. That's the “fabric of society”of Kei Islands.Keywords: Ain ni Ain, Kinship, Plurality Value, Structural, Functional, Society, Kei-Evav